HEALTH LITERACY ON HYPERTENSION AND FUNCTIONAL HEALTH STATUS AMONG ELDERLY OF MALABON CITY, PHILIPPINES - Mangada, Miguel E; Ogabang, Mary Jane (PEOPLE: International Journal of Social Sciences, 2019)
Hypertension is an important risk factor for cardiovascular morbidity and mortality in the elderly. Utilizing cross-sectional research design, this study determined health literacy on hypertension and functional health status among elderly of Malabon City, Philippines. Findings revealed that a) majority of respondents were females, between 65-69 years old, received allowances from relatives, graduated elementary, lived with relatives, did not smoke nor drink alcohol, and hypertension, their most common existing disease; b) no difference existed in heath literacy among respondents when grouped according to age, gender economic support source, living status and co-morbidity); c) difference existed between health literacy and education, smoking and alcohol consumption; d) no difference existed between physical health status, living status (P=0.098) and co-morbidity; e) difference existed between physical health status and age, gender, economic support source, education., smoking, and alcohol consumption; f) no difference existed between psychological health status and age, economic support source, educational, living status, smoking, alcohol consumption and co-morbidity; g) difference existed between psychological health status and gender; h) no difference existed in social/role health status when grouped according to gender, economic support source, smoking, alcohol consumption and co-morbidity; i) difference existed between social/role health status and age, education and living status; j) no relationship existed between health literacy and physical health status; k) no relationship existed between health literacy (Pearson r; lastly, l) no relationship existed between health literacy and social role. In conclusion, sociodemographic characteristics of the elderly do not impact on their knowledge about hypertension as well as on their physical, psychological and social functioning.